ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN OPINI AUDIT GOING CONCERN (Studi Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2018) - Virky Septiani Putri; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2021)
These research aims are to analyze and provide empirical evidence of the influence of audit tenure, audit lag, opinion shopping, liquidity, leverage, and debt default to the acceptance of going concern opinion. The population used in this research is manufacturing companies listed on The Indonesia Stock Exchange (IDX) in 2014-2018. Samples were selected using a purposive sampling method. 128 companies are selected to be samples. This research used regression analysis as analyze of method and SPSS 20.The results from this research showed audit tenure and liquidity have a negative significant effect on the acceptance of going concern opinion, audit lag, leverage, and debt default have a positive significant effect, while opinion shopping does not affect the acceptance of going concern opinion.